WELFARE PACKAGES AND JOB SATISFACTION AMONG PUBLIC SECONDARY SCHOOOL TEACHERS’ ONDO STATE, NIGERIA - Oyetakin, Akinrotimi Iyiomo; Ajalode, Joseph Alaba; Alen, Temidayo (UNIZIK Journal of Educational Management and Policy, 2019)
The study investigated the relationship between the level of welfare packages and teachers’ job satisfaction among public secondary school teachers in Ondo State, Nigeria. A descriptive research design of a survey type was adopted for guide the study. The population of the study consisted of all the 16 public secondary schools in Akoko North East Local Government Area of Ondo State. To generate sample for the study, the simple random sampling technique was employed to sample one principal and nineteen teachers from 30 public secondary schools where a total sample of six hundred (600) respondents comprising 30 principals and 570 teachers was used for the study. The instrument for data collection was a researcher-developed questionnaire titled, “Welfare Packages and Job Satisfaction of Teachers Questionnaire (WPJSTQ) which was validated by experts. It was tested and found reliable at r-0.87.The findings of the study showed that there is a significant relationship between teachers’ welfare packages and job satisfaction in secondary schools. It also was also found out that there is no significant relationship between internal welfare packages factors and teachers’ job satisfaction in Ondo state secondary schools and as that there is a significant relationship between external welfare packages and job satisfaction in secondary schools. Following the findings, it was recommended that involvement of teachers in decision making should be a practice of modern day principals. It was also recommended that to increases teachers’ job satisfaction and achievement in secondary schools, it is important that the Government should increase its budgetary allocation to education and to adequately allocate sufficient funds to secondary schools for the provision of necessary materials and equipment.